PENERAPAN STANDAR GRI DALAM LAPORAN KEBERLANJUTAN DI INDONESIA: SEBUAH EVALUASI - Randy Kuswanto (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
This study aims to investigate the level of conformity of economic, social, and environmental information on sustainability report in Indonesia as per GRI G4 guidelines. Content analysis has been applied to a sample of 29 companies listed in the Indonesia Stock Exchange. Conformity and disclosure quality were analyzed descriptively using a specific scoring system for each dimensions. The findings of this research show that the level of conformity of GRI indicators in Indonesia is quite low at 18,9%. However, the weight of information disclosed by companies is relatively high, at 59,9% of the information. This wide gap occurred caused by the fact that many companies disclose only a few indicators of GRI G4. These findings indicate the GRI G4 Guidelines is not really suitable for company in Indonesia. One of the primary focuses of this research is the applicability of GRI indicators. However, not even a single study found while reviewing literature that studied the applicability GRI indicators in a country. Conformity can become a new topic when studying accounting information disclosure.